Molecular Forms of Human Protein C: Comparison and Distribution in Human Adult Plasma - Greffe, Brian S; Manco-Johnson, Marilyn J; Marlar, Richard A (Thrombosis and Haemostasis, 1989)
Protein C (PC) is a vitamin K-dependent protein which functions as both an anticoagulant and profibrinolytic. It is synthesized as a single chain protein (SC-PC) and post-transla-tionally modified into a two chain form (2C-PC). Two chain PC consists of a light chain (LC) and a heavy chain (HC). The present study was undertaken to determine the composition of the molecular forms of PC in plasma. PC was immunoprecipitated, subjected to SDS-PAGE and Western blotting. The blots were scanned by densitometry to determine the distribution of the various forms. The percentage of SC-PC and 2C-PC was found to be 10% and 90% respectively. This is in agreement with previous work. SC-PC and the heavy chain of 2C-PC consisted of three molecular forms (“alpha”, “beta”, and “gamma”). The “alpha” form of HC is the standard 2C form with a MW of 40 Kd. The “beta” form of HC has also been described and has MW which is 4 Kd less than the “alpha” form. The “gamma” species of the SC and 2C-PC has not been previously described. However, its 3 Kd difference from the “beta” form could be due to modification of the “beta” species or to a separate modification of the alpha-HC. The LC of PC was shown to exist in two forms (termed form 1 and form 2). The difference between these two forms is unknown. The molecular forms of PC are most likely due to a post-translational modification (either loss of a carbohydrate or a peptide) rather than from plasma derived degradation.
Keywords: Protein C; Thrombosis; Coagulation; Protein processing